ANALYSIS OF THE FEASIBILITY OF WOOD WORKSHOP FACILITIES AND INFRASTRUCTURE THROUGH THE VIRTUAL LABORATORY CONCEPT IN PREPARING EMPLOYABILITY SKILLS FOR PROSPECTIVE VOCATIONAL SCHOOL TEACHERS - Liana Atika; Zhilli Izzadati Khairuni; Riansyah Putra; Syafiatun Siregar; Mena Fadilla Lukman; Dhimas Ridho; Safrinanda Harahap (LPPM Universitas Negeri Jakarta, 2025)
This study aimed to determine the feasibility of the wood workshop area in the Wood Stone and Plumbing Workshop, Faculty of Engineering, State University of Medan, based on the required standards. This is done to provide comfort for users of the Wood Stone and Plumbing Workshop, Faculty of Engineering, State University of Medan. This study is a type of research with a descriptive, evaluative method. The subjects in this study were the Wood Stone and Plumbing Workshop, the Faculty of Engineering, the State University of Medan, and the Wood Workshop. In contrast, the object of the study was the area of the Wood Workshop workspace, Faculty of Engineering. Data collection methods were by interview, observation, and documentation. The data analysis technique was carried out using a quantitative method, namely comparing the research data at the Wood Stone and Plumbing Workshop, Faculty of Engineering, State University of Medan, with existing standards and supported by the results of field observations. The results of this study are that the area of the Wood, Stone and PlumbingWorkshop workspace at the Faculty of Engineering, State University of Medan meets the space standards, namely 128 m2, which is smaller than the standard size of 256 m2, and the area of the instructor's room at the Wood, Stone and Plumbing Workshop, Faculty of Engineering, State University of Medan does not meet the space standards, 40 m2, which is smaller than the standard size of 48 m2.